Tampering with cancer chemoresistance by targeting the TGM2-IL6-autophagy regulatory network. Issue 3 (4th March 2017) - Zhang, Han; McCarty, Nami
ABSTRACT: Macroautophagy/autophagy is a well-established process involved in maintaining cellular homeostasis, but its role in cancer is complex and even controversial. Many studies have reported a correlative relationship between increased autophagy and evolving cancer cells under stress conditions such as nutrient or oxygen deprivation; however, there has been a lack of a plausible mechanistic link to properly target the autophagy process in the context of this microenvironment. We recently unveiled a positive regulatory loop involving TGM2 (transglutaminase 2)-NFKB/NF-κB signaling, IL6 and autophagy in cancer using mantle cell lymphoma (MCL) as a model system. These pathways are functionally connected to each other, thereby promoting malignant B cell survival and leading to enhanced lymphoma progression both in mice and in patients. Disruption of this network could provide an opportunity to increase the efficacies of current therapies and to reduce MCL drug resistance.